Clinical importance of pharmacogenetic polymorphisms affecting drug metabolism - Stingl (formerly Kirchheiner), Julia (Henry Stewart Talks, 2007)
Genetic variability in pharmacokinetics, Polymorphic drug-metabolizing enzymes (Cytochrome P450), Implementation of pharmacogenetics in drug therapy, Risks and benefits of being a poor metabolizer, Limitations of genetics-based dose adjustments, Future clinical study directions in pharmacogenetics
Updated at 2016/07/31